Effects of low-dose acetylsalicylic acid and atherosclerotic vascular diseases on the outcome in patients with severe sepsis or septic shock. (September 2013) - Otto, Gordon Philipp; Sossdorf, Maik; Boettel, Janina; Kabisch, Björn; Breuel, Hannes; Winning, Johannes; Lösche, Wolfgang
<x xml:space="preserve">Abstract</x> Sepsis and its sequelae of multiple organ failure is one of the leading causes of death in the industrial countries. Several studies have shown that patients who are treated with low-dose acetyl salicylic acid (ASA) for secondary prevention of atherothrombosis may have a lower risk to develop organ failure in the case of critical illness. The benefit of ASA is probably due to an inhibition of platelet activation as well as an increase in the formation of anti-inflammatory lipoxin A4. On the other hand, the effect of ASA could be – at least partially – an indirect one, caused by atherosclerotic vascular diseases as the cause of ASA treatment. Atherosclerosis is considered as a moderate systemic inflammation and we hypothesise that this chronic condition could have an impact on the outcome in sepsis. To get more information on the benefit of ASA in critically ill patients and on possible interference with atherosclerotic vascular diseases, we analysed the medical records of 886 septic patients who were admitted to the surgical intensive care unit (ICU) of a university hospital. Logistic regression analysis indicated that patients who were treated during the ICU stay with ASA (100 mg/d) had a significantly lower mortality. Odds ratios (ORs; with 95% confidential intervals) of 0.56 (0.37–0.84) and 0.57 (0.39–0.83) were calculated for ICU and hospital mortality, respectively. In contrast, statin treatment did not have significant effect on mortality. Diagnosis of atherosclerotic vascular diseases according to ICD classification did not influence ICU mortality but lowered hospital mortality (OR = 0.71 (0.52–0.99)). Subgroup analysis provided preliminary evidence that clopidogrel when given as only anti-platelet drug may have a similar benefit as ASA, but the combination of ASA and clopidogrel failed to improve the outcome. The time course of plasma fibrinogen and procalcitonin levels indicate that ASA seems to reduce the activation of haemostasis and increase the resolution of inflammation. It is concluded that prospective interventional studies should be done to test the use of ASA as novel therapeutic approach in critically ill patients.